Analisis Faktor Determinan Terhadap Perilaku Pemilihan Jajanan Pada Murid Sekolah Dasar - Audya Titah Amalsha; Linda Riski Sefrina (Jurnal GIZIDO, 2022)
According to FAO (2006), street food is food and beverages prepared or sold by street vendors on the streets and in public places which are directly consumed without further processing or preparation (Warlenda and Desnovianti, 2018). Some tests say that most of the snacks are not in accordance with food safety quality standards. In general, snacks in the canteen and food vendors around the school environment contain flavors or other additives that are not good if consumed too often and contain dust or other microbes. There needs to be an attitude in choosing snacks for elementary school students so that students are more selective about the snacks they will consume and train critical thinking skills in elementary school students. The purpose of writing this study is to determine the determinant factors associated with the selection of snacks in elementary school students. The method used in this research is library search. The results showed that the determinant factors for choosing snacks were the characteristics of snacks, food familiarity factors, environmental factors, and economic factors related to the provision of pocket money to elementary school students. Key words : behavior, determinant factors, elementary school students, snack selection